From evaluative to deontic predication: Evidence for the grammaticalization path from clausal complementation strategies - Holvoet, Axel (Kalbotyra, 2024)
A shift from evaluation (‘it is good, fitting’, etc.) to deontic modality is well known from the literature on grammaticalization. This article looks at it from the viewpoint of complementation. In Lithuanian, a complementation strategy characteristic of evaluative predicates has been carried over to deontic contexts. The complementation strategy referred to consists in the reuse of an originally conditional adverbial clause structure with evaluative predicates as a means of avoiding the factive implication usually associated with evaluatives (cf. it is good that... : it would be good if...). The conditional clause type under discussion contains the anteriority converb in -us, which, as a result of the shift ‘evaluative → deontic’, has become characteristic of a set of deontic constructions where it competes with the infinitive. This development moreover involved processes of insubordination and resubordination. The relevance of the Lithuanian facts (apart from their intrinsic interest, also from the viewpoint of resubordination processes) consists in that the extension of the complementation type from evaluative to unambiguously deontic contexts provides palpable proof of the transition while the research has hitherto failed to find a cut-off point between evaluation and deontic modality.
Keywords: evaluative predicates; deontic modality; complementation strategies; insubordination; resubordination